Strategies for Child Marriage Prevention in Indonesia: A Case Study - Enny Fitriahadi; Thuy Hong Nguyen; Endang Koni Suryaningsih; Evi Wahyuntari; Yekti Satriyandari (Jurnal Kesehatan Masyarakat, 2025)
Early marriage is a complex social problem, with many girls marrying before the age of 18. In Indonesia, child marriage data in 2021 increased by 30%. This figure indicates that early marriage remains a significant challenge in Indonesia, in terms of education and health. This study aims to explore perceptions about child marriage and provide insight into the dynamics of decision-making around child marriage in Dlingo and Dukun, Indonesia. Qualitative research methods were used to ensure an in-depth understanding of the reasons and processes behind child marriage. Data were collected through 12 focus group discussions (FGD), 20 in-depth interviews (IDI), and 6 semi-structured key interviews (KII) informants. The instrument used a semi-structured guideline, using individual interview techniques. Data analysis used Nvivo version 12. This study concluded that families use child marriage as a protection strategy in response to economic insecurity. In addition, this program is also used as a means to protect young women from sexual exploitation and prevent consensual sex before marriage. Early marriage is associated with the vulnerability of pregnancy complications, while the recommendation is to provide comprehensive education to adolescents about reproductive health and the dangers of early marriage.